Impacto de las Abejas (Apis mellifera L.) Como Agentes Polinizadores en el Rendimiento del Cultivo de Zucchini (Cucurbita pepo L.) en el Canton Riobamba, Provincia de Chimborazo - M. J., Herrera Villalobos; V. A., Lindao Córdova; A. E., Espinosa Espinosa; E. R., Carrera Guanoluisa; J., Yanéz Villacís (European Scientific Journal, ESJ, 2019)
The impact of bees (Apis mellifera L.) as pollinators in the yield of the zucchini (Cucurbita pepo L.) crop in the Riobamba canton, Chimborazo province, was evaluated using a Randomized Complete Block Design (RCBD). This was done using three treatments and three repetitions. The treatments evaluated were: the zucchini cultivation inside the micro tunnel covered with entomological mesh with the presence of bees, the zucchini cultivation inside the micro tunnel covered with anti aphids mesh without the presence of bees, and the open field zucchini cultivation. The evaluated parameters were number of days to the appearance of the fruits, percentage of fertilized and unfertilized flowers, number of fruits per plant, size of fruits, diameter of fruits, weight of fruit, and yield in kg / ha per treatment. The best results achieved in most parametersthat were evaluated such as the percentage of flowering, number of fruits per plant, size of fruit in cm, diameter of fruit in cm, weight of the fruit in grams, yield in kg/ha by treatment, and economic analysis were obtained with the presence of bees (Apis mellifera L.) as pollinating agents in the tunnel. This is in addition to meshes during the flowering stage of the zucchini crop, with an average yield of 14.9 tn/ha. Se evaluó el impacto de las abejas (Apis mellifera L.) como agentes polinizadores en el rendimiento del cultivo de zucchini (Cucurbita pepo L.) en el cantòn Riobamba, provincia de Chimborazo. Para llevar a cabo esta evaluación se utilizó un diseño de bloques completos a azar (DBCA), con tres tratamientos y tres repeticiones. Los tratamientos evaluados fueron: El cultivo de zucchini dentro del micro túnel cubierto con malla entomológica con presencia de abejas, el cultivo de zucchini dentro del micro túnel cubierto con malla antiáfidossin presencia de abejas y el cultivo de zucchini a campo abierto. Los parámetros evaluados fueron número de días transcurridos después de la aparición de los frutos, porcentaje de flores fecundadas y no fecundadas, número de frutos por planta, tamaño de frutos, diámetro de frutos, peso del fruto y rendimiento en kg/ha por tratamiento. Los mejores resultados alcanzados en la mayoría de los parámetros evaluados como el porcentaje de floración, número de frutos por planta, tamaño de fruto en (cm), diámetro de fruto en (cm), peso del fruto en gramos, rendimiento en kg/ha por tratamiento y análisis económico, se obtuvieron con la presencia de las abejas (Apis mellifera L.) como agentes polinizadores en el túnel con mallas durante la etapa de floración del cultivo de zucchini, con un rendimiento en promedio de 14.9 tn/ha.